1976
DOI: 10.1002/pol.1976.180141012
|View full text |Cite
|
Sign up to set email alerts
|

Studies of molecular relaxation of poly(propylene oxide) solutions by dielectric relaxation and brillouin scattering

Abstract: Dielectric relaxation and Brillouin scattering are jointly used in studying molecular relaxation in poly(propylene oxide) (PPO) and its solutions in methylcyclohexane. The dielectric method was applied to the more concentrated (100%, 80%, 60%, by volume) solutions over a wide temperature and frequency range (30 Hz to 8 GHz) in order that the variation in activation energy characteristic of a glass‐forming substance could be delineated. The present work extends previous work on the undiluted polymer to higher f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 11 publications
(1 reference statement)
2
19
0
Order By: Relevance
“…The spectral fit provides the a' and TS values at these temperatures. Similar to that found in alcohols, I3 the TS values obtained at temperatures around the linewidth maximum follows the Arrhenius temperature dependence: with 'To and Ea determined from the spectra around the linewidth maximum, and assuming Ws = w~ (I -bT) (20) determined from the high temperature Brillouin frequency data, one can now simultaneously fit the experimental values of IB and r Busing Eqs. (17) and (18), keeping only Rand r b as free parameters.…”
Section: Shown Inmentioning
confidence: 70%
“…The spectral fit provides the a' and TS values at these temperatures. Similar to that found in alcohols, I3 the TS values obtained at temperatures around the linewidth maximum follows the Arrhenius temperature dependence: with 'To and Ea determined from the spectra around the linewidth maximum, and assuming Ws = w~ (I -bT) (20) determined from the high temperature Brillouin frequency data, one can now simultaneously fit the experimental values of IB and r Busing Eqs. (17) and (18), keeping only Rand r b as free parameters.…”
Section: Shown Inmentioning
confidence: 70%
“…In 1976 Yano et al [5] reported new dielectric data on PPO in bulk and solutions in methylcyclohexane. The dielectric relaxation (DR) measurements were performed in a very broad range of frequencies (log f max (Hz) ¼ À3 to 9.5) and were combined with Brillouin scattering.…”
Section: Introductionmentioning
confidence: 98%
“…However, PPO, because of its noncrystallizability and availability in a wide molecular weight range, is acceptable as a model object for close examination of relaxation properties of flexible chain polymers. Its relaxation characteristics, basically those of the corresponding low molecular weight OH-ended analogue, so-called poly(propylene glycol) (PPG), have been intensively studied using dielectric, [1][2][3][4][5][6] optical, 7-10 nuclear magnetic resonance (NMR), [11][12][13] quasi-elastic neutron scattering, 14,15 and ultrasonic, [16][17][18][19][20][21] techniques, as well as various methods for probing viscoelastic properties. [22][23][24] In contrast to PPO, PEO and PTMO are possible to crystallize and they can be closely investigated only in a temperature range above the melting point.…”
mentioning
confidence: 99%